On the Model of Prognosis of Proceeds of Industrial Enterprises - E.L. Pankratov (Budapest International Research and Critics University, 2020)
In modern economic theory, scientific and technological progress considers as one of the relevant factors of long-term eco-nomic growth. The influence of scientific and technological progress on a particular sector of the economy appears in the creation of new products that have important competitive advantages over existing ones, or in the modification (modernization) of existing products. Often, new products based on new (innovative) technologies. However, technological superiority requires well-timed modernization of production and staff training, that is, significant financial and organizational investments. At the same time, the rejection of the transition to innovative technologies can lead to tangible losses in market positions or even to a complete cessa-tion of the organization. This model gives a possibility to make a prognosis of proceeds of enterprises with account changing of quantity of manufactured products, as well as various expenses (raw materials, transportation costs,...). An analytical approach for analyzing the influence of various parameters on the proceeds has been introduced.